Mediatization of a Research Group: The Estonian Student Satellite ESTCube-1. Issue 2 (April 2019) - Olesk, Arko
Increased interactions between researchers and the media can change the individual and collective practices in science due to the considerations about media logic. This article uses the example of the team behind the Estonian satellite ESTCube-1 to describe the process of mediatization and its impacts on the research project. The quick and extensive adaption to media logic by the team can be attributed to the interplay of three elements: the role of the group leader, participation in media trainings, and regular interactions with the media. This article provides a model of how micro-level mediatization is likely to take place in science.